Use of methylmalonyl‐CoA epimerase in enhancing crotonase stereoselectivity - Hamed, R; Gomez-Castellanos, J; Sean Froese, D; Krysztofinska, E; Yue, W; Schofield, C (Wiley, 2015)
The use of methylmalonyl‐CoA epimerase (MCEE) to improve stereoselectivity in crotonase‐mediated biocatalysis is exemplified by the coupling of MCEE, crotonyl‐CoA carboxylase reductase and carboxymethylproline synthase in a three‐enzyme one‐pot sequential synthesis of functionalised C‐5 carboxyalkylprolines starting from crotonyl‐CoA and carbon dioxide.